Climate variability impact on water requirement of spring maize in central and sub-mountainous Punjab - Majumder, Debjyoti; Kingra, P.K.; Singh, Sompal (Annals of Agricultural Research, 2016)
Long-term variability in potential evapotranspiration (PET) of spring maize during the period 1985- 2014 was assessed for two agroclimatic regions i.e. Ludhiana representing central plain region and Ballowal Saunkhari representing sub-mountainous agroclimatic region of Punjab. PET of spring maize has been observed to increase over years at both the locations @ 1.3 mm year–1 at Ludhiana and 2.9 mm year–1 at Ballowal Saunkhari. During the period of three decades, Ludhiana experienced lowest of 693.0 mm of PET during 1997 and highest 931.9 mm during 2010, while, Ballowal Saunkhari experienced lowest PET of 723.7 mm during 1992 and a highest of 954.7 mm during 2010 during the growing period of spring maize. Day time temperature was found to have positive correlation with PET of spring maize at Ludhiana (r = 0.87) and Ballowal Saunkhari (r = 0.90). Similarly, morning and evening RH were negatively correlated with PET at Ludhiana (r = –0.56 and –0.42) and Ballowal Saunkhari (r = –0.36 and –0.31). Multiple regression models explained 75 to 82 per cent variation in PET of spring maize at Ludhiana and 79 to 90 per cent variability at Ballowal Saunkhari because of the weather parameters. The study indicates that increase in water requirements under warming scenarios will put more pressure on already depleting water resources in the state and hence need to be managed in view of changing climatic conditions.